The interplay between teamwork, clinicians’ emotional exhaustion, and clinician-rated patient safety: a longitudinal study - Welp, Annalena (Crit Care, 2016)
BACKGROUND: Effectively managing patient safety and clinicians’ emotional exhaustion are important goals of healthcare organizations. Previous cross-sectional studies showed that teamwork is associated with both. However, causal relationships between all three constructs have not yet been investigated. Moreover, the role of different dimensions of teamwork in relation to emotional exhaustion and patient safety is unclear. The current study focused on the long-term development of teamwork, emotional exhaustion, and patient safety in interprofessional intensive care teams by exploring causal relationships between these constructs. A secondary objective was to disentangle the effects of interpersonal and cognitive-behavioral teamwork. METHODS: We employed a longitudinal study design. Participants were 2100 nurses and physicians working in 55 intensive care units. They answered an online questionnaire on interpersonal and cognitive-behavioral aspects of teamwork, emotional exhaustion, and patient safety at three time points with a 3-month lag. Data were analyzed with cross-lagged structural equation modeling. We controlled for professional role. RESULTS: Analyses showed that emotional exhaustion had a lagged effect on interpersonal teamwork. Furthermore, interpersonal and cognitive-behavioral teamwork mutually influenced each other. Finally, cognitive-behavioral teamwork predicted clinician-rated patient safety. CONCLUSIONS: The current study shows that the interrelations between teamwork, clinician burnout, and clinician-rated patient safety unfold over time. Interpersonal and cognitive-behavioral teamwork play specific roles in a process leading from clinician emotional exhaustion to decreased clinician-rated patient safety. Emotionally exhausted clinicians are less able to engage in positive interpersonal teamwork, which might set in motion a vicious cycle: negative interpersonal team interactions negatively affect cognitive-behavioral teamwork and vice versa. Ultimately, ineffective cognitive-behavioral teamwork negatively impacts clinician-rated patient safety. Thus, reducing clinician emotional exhaustion is an important prerequisite of managing teamwork and patient safety. From a practical point of view, team-based interventions targeting patient safety are less likely to be effective when clinicians are emotionally exhausted.